Językoznawstwo kognitywne w nauczaniu języków obcych: projekt gramatyki - Kwapisz-Osadnik, Katarzyna (Neofilolog, 2010)
The article focuses on a visual grammar project, a strategy which uses notions of cognitive and semantic schemes, the use of prototype and semantic invariant described by cognitive linguistics. The article also includes suggestions concerning the use of the method to teach the French subjunctive.